Circulating plasmablasts and high level of BAFF are hallmarks of minimal change nephrotic syndrome in adults. Issue 4 (30th November 2020) - Oniszczuk, Julie; Beldi-Ferchiou, Asma; Audureau, Etienne; Azzaoui, Imane; Molinier-Frenkel, Valérie; Frontera, Vincent; Karras, Alexandre; Moktefi, Anissa; Pillebout, Evangeline; Zaidan, Mohamad; El Karoui, Khalil; Delfau-Larue, Marie-Hélène; et al.
Abstract: Background: The recent success achieved with the use of B cell-depleting agents in some patients with minimal change nephrotic syndrome (MCNS) suggests an unexpected role for B lymphocytes in the pathogenesis of this immune-mediated glomerular disease. Nevertheless, no extensive B-cell phenotyping analysis has ever been performed in untreated adult patients soon after MCNS diagnosis. Methods: We investigated the distribution of the different B-cell subpopulations in 22 untreated adult patients with biopsy-proven MCNS [MCNS relapse (MCNS-Rel)]. We compared these data with those for 24 healthy controls, 13 MCNS patients in remission (with no specific treatment) and 19 patients with idiopathic membranous nephropathy (IMN). Results: Patients with MCNS-Rel or IMN had higher proteinuria and lower serum albumin and gammaglobulin levels (P < 0.0001 for all comparisons) than MCNS patients in remission. Plasmablasts were the only B-cell subsets present at significantly higher levels in MCNS-Rel patients than in the patients of the other three groups (P < 0.05 for all comparisons). The lower albumin levels and higher proteinuria levels were positively correlated with the percentage of circulating plasmablasts (Spearman test's ρ = −0.54, P = 0.01 and ρ = 0.65, P = 0.002, respectively). Similarly, the increase of immunoglobulin M (IgM) and the decrease of IgG levels were significantly associated with the percentage of plasmablasts in MCNS-Rel patients (Spearman's ρ = 0.36, P = 0.01 and Spearman's ρ = −0.60, P = 0.01, respectively). Increased production of interleukin (IL)-21, IL-6 and B-cell activating factor (BAFF) in the serum of MCNS-Rel patients was found significantly correlated with the percentage of plasmablasts (ρ = 0.72, P = 0.0002, ρ = 0.49, P = 0.04 and ρ = 0.62, P = 0.009, respectively). Conclusions: An increase in the proportion of circulating plasmablasts seems to be a hallmark of untreated MCNS in adult patients. Further studies are required to more precisely determine the phenotype and functions of these cells.